Inheritance of Consonant Phonemes from PAN to Mandailing Language - Fitri Rosalina Harahap (Tradition and Modernity of Humanity, 2024)
This study aims to examine the inheritance of consonant phonemes from Proto-Austronesian (PAN) to Mandailing Language (BM), as part of the Austronesian language family. The method used is the comparative historical method with a focus on analyzing basic Swadesh vocabulary collected from native speakers in Panyabungan, Mandailing Natal. The diachronic analysis shows that BM preserved some phonemes from PAN while undergoing significant changes in some consonants. The results show patterns of phonetic changes of PAN to BM consonants, including changes of /b/ to /b/ or /m/, /k/ to /h/ in the penultima position, /z/ to /j/ in the ultima position, /l/ to /n/ in the ultima position, and changes of /h/ to missing in the ultima position. These changes provide deep insights into phonological evolution in BM, indicating a PAN linguistic heritage with innovative variations in word phonology and morphology. The findings support the theory of language evolution and make an important contribution to the understanding of Austronesian historical linguistics.